Reducing transfer times for coronary angiography in patients with acute coronary syndromes: one solution to a national problem. Issue 968 (5th June 2006) - Bellenger, N G; Wells, T; Hitchcock, R; Watkins, M; Duffet, C; Jewell, D; Palliser, D; Shapland, L; Curtis, R; Scrase, S; Burns, R; Curzen, N
Abstract : Backgound: Patients with acute coronary syndrome (ACS) are at high risk of further cardiac events and benefit from early intervention, as reflected by international guidelines recommending early transfer to interventional centres. The current average waiting time of up to 21 days contravenes evidence based early intervention, creates geographical inequity of access, wastes bed days, and is unsatisfactory for patients. Methods: A regional transfer unit (RTU) was created to expatiate access of ACS patients referred from other centres to the revascularisation service. By redesigning the care pathway patients arriving on the RTU undergo angiography within 24 hours, and then leave the RTU the following day, allowing other ACS patients to be treated. Results: During the first six months of the RTU, the mean waiting time from referral to procedure decreased from 20 (SD 15) days (range 0–51) to 8 (SD 3) days (range 0–21) for 365 patients transferred from a distict general hopsital. Ninety seven per cent of patients underwent angiography within 24 hours, 61% having undergone percutaneous coronary intervention at the same sitting, and 78% were discharged home within 24 hours. Conclusions: Delivering standards laid out in the National Service Framework, reducing inequalities of care across the region, and facilitating evidence based strategies of care represents a challenging and complex issue. For high risk patients suffering ACS who need early invasive investigation, a coordinated network wide approach together with the creation of an RTU resulted in a 62% reduction in waiting times for no extra resources. Further improvements can be expected through increased capacity of this verified strategy.